Highly efficient activation of peroxymonosulfate by Co3O4/Bi2WO6 p-n heterojunction composites for the degradation of ciprofloxacin under visible light irradiation - Sun, Jie; Shen, Chun-Hui; Guo, Jie; Guo, He; Yin, Yi-Fei; Xu, Xin-Jie; Fei, Zheng-Hao; Liu, Zong-Tang; Wen, Xiao-Ju (Journal of colloid and interface science, 2021)
[Display omitted] Photocatalytic technology assisted via peroxymonosulfate (PMS) has good potential in water treatment. In this study, the Co3O4/Bi2WO6 composite was constructed via an in-situ calcination process and used to activate PMS for the degradation of ciprofloxacin (CIP) under visible light irradiation. The obtained 5 wt% Co3O4/Bi2WO6(CBWO-2) can highly effectively remove 86.2% CIP within 5 min visible light irradiation in presence of PMS. The excellent degradation performance of Co3O4/Bi2WO6/PMS system can be attributed to the synergistic effect between p-n heterojunction and PMS activation. The conduction band and valence band deviation between Co3O4 and Bi2WO6 were calculated by XPS techniques. Besides, DFT calculations were performed to further confirm the internal structure between Co3O4 and Bi2WO6. This work not only provides an approach to fabricate heterostructures but also indicated that Co3O4/Bi2WO6/PMS/Vis system is a potential environment remediation alternative for the efficient removal of recalcitrant organic compounds from wastewaters.